Model of Training Using Rubber To Improve Under Passing Volleyball Ability - Wanto Maryanto; Dicky Reva Apriana Sanga Dwi (STKIP Muhammadiyah Kuningan, 2019)
This research aims to determine the extent to which the modification of the rubber aids increases the ability to pass under the volleyball extracurricular members of the One Roof Patala Junior High School, using the RnD from Borg and Gall. The sample in this research amounted to 20 people, which began with giving instructions to perform the pretest. After that, he was given a volleyball underpass exercise model with rubber modifications for 14 times, then his under-passing skills were again tested. The results of the study obtained test, then performed the pre-post test normality test and paired sample T-test data. The results of the study before the sample were given treatment, the average value of the treatment group was 11.20 and the control group was 8.90, while after being given the training model the results of the treatment group were 16.50 and the control group was 8.90. The results of the Paired Sample T-Test treatment class data obtained show that the pre-test and post-test results on the Braddy Volley Ball Test obtained Asymp values. Sig. (2-tailed), which is equal to 0,000, less than α = 0.05. This result is smaller than α = 0.05, so the research data is significant.